If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 7(3 + -2x) + -6(4 + -3x) 9 = (3 * 7 + -2x * 7) + -6(4 + -3x) 9 = (21 + -14x) + -6(4 + -3x) 9 = 21 + -14x + (4 * -6 + -3x * -6) 9 = 21 + -14x + (-24 + 18x) Reorder the terms: 9 = 21 + -24 + -14x + 18x Combine like terms: 21 + -24 = -3 9 = -3 + -14x + 18x Combine like terms: -14x + 18x = 4x 9 = -3 + 4x Solving 9 = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 9 + -4x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 9 + -4x = -3 + 0 9 + -4x = -3 Add '-9' to each side of the equation. 9 + -9 + -4x = -3 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = -3 + -9 -4x = -3 + -9 Combine like terms: -3 + -9 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| X^2+-22x+120=0 | | -9+2x=15 | | 21x-9-14X+3=22X-7-15X+11 | | -15-2t=11 | | 144x^2-528x+114=0 | | 3n-2=-14 | | 142+2.7x=3571 | | 39=1.5x | | z^2+28z+192=0 | | 5x-2+78=180 | | 4-2(3-w)=18 | | (4x^2)+5x-9=0 | | 3-x=-10 | | 9x-7=9(x-7) | | 142+2.7x=7000 | | 5a=0.35 | | 4x+2=3(x-6)+6 | | (5p-5)(7p+6)= | | 8x+6-9x=2-15 | | -6m=-72 | | 3(6-b)-(-5)=-7 | | 42+(-81)+63-(58)-77= | | 7x+7-9x=15-19x+17x-8 | | 6x-7y=16 | | -15=y+15 | | 3-2[5-3(x+1)]=4x-10 | | 6p=p-40 | | (4x^2)+37x+75=0 | | z^2+13z+36=0 | | X^2-8x+84=0 | | 3x-10=2x+18 | | -x-24=5+x |